Profitability Of Companies Listed On The Portfolio Ise – Business Sustainability Index Of B3 – Brazil Balcony Bag (Research, Society and Development, 2019)
This research presents as theme the profitability of the companies listed in the ISE - Corporate Sustainability Index. The general objective is to investigate whether the companies that are part of the ISE portfolio of the clothing, telephony and food industry segments in the years 2015 to 2017 presented a return and financial security for the shareholders. As for the methodology, this is a quantitative, documental and exploratory descriptive research. The data that compose the sample of this present research were collected through the financial statements of 19 companies listed in B3 for the years 2017, 2016 and 2015. The liquidity, indebtedness and economic indices are calculated to investigate whether companies classified in ISE economic and financial performance. To test whether the ISE component companies are more profitable, less indebted and have a better financial situation, the T-Student test is used. In the analyzes referring to the financial security indicators, it is stated that the companies participating in the ISE have a greater capacity to honor their commitments with or without dependence on their inventory, but in the analysis of dry liquidity under the standardized criteria of significance level, the averages are the same. In relation to the level of indebtedness, listed companies have a greater record of short-term debt and, on the other hand, non-ISE companies are more dependent on third-party capital. However, the study evidences a higher profitability of the companies included in the ISE portfolio and proves the viability for shareholders to invest in companies that are classified by the ISE.Incluir o resumo em inglês.